Synthesis and application of dual-curable PVB based adhesive formulations for cord/rubber applications - YILDIZ, ZEHRA (TAYLOR & FRANCIS LTD, 2017)
In this research, formaldehyde-free dual-curable adhesive formulations containing polyvinyl butyral (PVB) were prepared with the reaction of 2,4-toluene diisocyanate (TDI) and 2-hydroxyethyl methacrylate (HEMA) and then applied on cord fabrics upon adhere onto the rubber surfaces. The effects of PVB ratio on peel strength value between the cord and rubber were studied. The structure of the oligomer was characterized by FTIR and H-1 NMR spectroscopy. Thermal properties of coated and UV-cured fabrics were investigated by TGA and DSC. Surface wettability properties of the fabrics after coating were observed with contact angle measurement. The peel strength between cord/rubber surfaces was determined by T-peel test after thermal curing stage under heat and pressure. Results showed that peel strength value increases with increasing PVB amount in the formulation. The highest peel strength of 94.7 N/cm was observed when 5% PVB was included in the formulation. This study leads to a new type of promising adhesives with superior peel strength for cord/rubber applications as it is being a totally formaldehyde-free process.
Keywords: Polyvinyl butyral; adhesion; cord fabric; styrene butadiene rubber; UV-curable; NITRILE RUBBER; DIISOCYANATE; BEHAVIORS; ACRYLATES; SYSTEM; ACID